Simulation model of signal reflected from subsurface object given the properties of concealing surface - D. V. Demyaniuk; K. N. Chugai; Ye. S. Maksimovitch (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The factors which has an effect on distribution of electromagnetic energy in concealing surface and model of signal that reflected from subsurface object which allows to take into account existing patterns and features of radar image formation were examined in the article.